Adaptation Strategy of Forage Crops to Climate Change - Harmini Harmini; A Fanindi (Indonesian Center for Animal Research and Development, 2020)
Climate change is characterized by an increasing in temperature, drought, and an increase in CO2. This paper aims to describe the strategy to deal with climate change in forage crops. Plant adaptation mechanisms include increasing water content, cell membrane stability, and photosynthetic capacity by suppressing stomata conductance and C consumption through respiration. The impacts of climate change on animal feed crops include: decreased productivity and nutrient content, and reduced planting area which affects the supply of animal feed so that food availability is disrupted. Adaptation strategies are carried out by managing the cultivation of forage plants, including selecting planting and harvesting times, as well as irrigation. Besides, it is necessary to select adaptive fodder plants through breeding. Breeding methods are conducted through the exploration of genetic resources to compile new superior forage adaptive crops to climate change.